Electrical Injuries: The Iceberg Phenomena - Manandhar, Krishna; Shrestha, Jayan Man; Rayamajhi, Sangam; Lohani, Ishwar (Journal of Society of Surgeons of Nepal, 2017)
Introduction: The deceptive nature of electrical injury is likened to an iceberg phenomenon. Whether the tissue is conductive or resistant both are injured due to electroporation and heat, respectively. The objective of the study is to evaluate the types and pattern of injuries and attempt to predict the chances of various types of injuries and highlight the iceberg phenomenon.Methods: A retrospective study includes 36 patients. Injuries were classified into superficial and deep. Total burned surface area (TBSA) was categorized into four, 20%. The depth of injury was categorized into superficial and deep. Deep injuries were elaborated into loss of skin, muscle, tendon, nerve, artery, cartilage and damage of bone and internal organs. Treatment was grouped into conservative and surgical, where surgical was classified into minor, major and amputation procedures.Results: Injuries were mostly located over the upper extremities (47.76%). The first TBSA category had the highest number of patients (64%), highest percent of superficial and deep injuries (63.88% and 61.29%, respectively) and highest percentage of procedures (64.25%). The average number of procedures per patient was 3.8. The median burned surface area (BSA) was 4% and most of the procedures were performed in patients with less than 4% BSA.Conclusion: Electrical injuries are truly iceberg phenomenon where a small area of TBSA hides the greatest percentage of the deep structure injuries and brings about surprising reconstructive challenges.